On The Geometric Interpretations of The Klein-Gordon Equation And Solution of The Equation by Homotopy Perturbation Method - Bulut, Hasan; Baskonus, H. Mehmet (Prairie View A & M Univ, Dept Mathematics, 2012)
This paper is organized in the following ways: In the first part, we obtained the Klein Gordon Equation (KGE) in the Galilean space. In the second part, we applied Homotopy Perturbation Method (HPM) to this differential equation. In the third part, we gave two examples for the Klein Gordon equation. Finally, We compared the numerical results of this differential equation with their exact results. We also showed that approach used is easy and highly accurate.
Keywords: The Galilean space; The Homotopy perturbation method; The Klein-Gordon Equation; Linear and nonlinear partial differential equations